Análisis de la cultura tributaria de los impuestos prediales en el cantón Chone en tiempos de Covid-19 período 2020-2021 - Robles Ostaiza, Angie Pierina (2023)
This investigation was developed in the Municipal Decentralized Autonomous Government in Chone Canton, to analyze the tax culture in property tax collection in Chone Canton during the COVID-19 period 2020-2021, to propose improvements in the collection management. This research was worked in three stages by applying the methods inductive, deductive, analytical-synthetic, historical, and statistical. In the first stage, techniques such as the survey were used, elaborated from the dimensions of reliability, responsiveness, and empathy, the same one that was directed to taxpayers to understand their degree of knowledge regarding the tax culture and identify to how much extent they have complied with the payment of their property taxes. In the second stage, an interview was conducted with the person in charge of the Coordination of the Internal Revenue Department of the municipality, managing to verify that they have many forms of payment such as agreements with banks, cancellation through Red Facilito and Western Union, website and mobile application, but there is no training on tax culture for citizens in general. Additionally, an analysis of the strengths, opportunities, weaknesses and threats existing in the process of collecting these municipal taxes was designed. In the third stage, an improvement plan was established, where the problems identified during the thesis work were visualized, as well as the possible strategies, activities, and goals that can be implemented to solve these difficulties in said public institution.